2022
DOI: 10.1089/jwh.2021.0121
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Preference for 3-Month Versus 1-Month Vaginal Rings for HIV-1 Risk Reduction Among Participants in a Phase 1 Trial

Abstract: Background: The monthly dapivirine vaginal ring provides partial protection against HIV, and a longer duration ring may reduce user burden and improve adherence. We examined acceptability and preference for 3-month versus 1-month rings for HIV-1 risk reduction in a phase 1 clinical trial. Materials and Methods: In Microbicide Trials Network-036/International Partnership for Microbicides 047, 49 HIV-negative participants aged 18–45 were randomized to one of two 3-month r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, the need for regular replacement every month poses adherence challenges especially in women under 25 years old (11). This prompted the development of a longer-acting ring (3 months) (12). Numerous subdermal long-acting implants are under preclinical investigation for HIV PrEP (10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, the need for regular replacement every month poses adherence challenges especially in women under 25 years old (11). This prompted the development of a longer-acting ring (3 months) (12). Numerous subdermal long-acting implants are under preclinical investigation for HIV PrEP (10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other PrEP studies, implant choices were primarily shaped by preference for less frequent dosing [ 22 , 28 32 ]. Although women noted that several other implant features were also important and, when asked directly, two-thirds indicated a feature other than duration was most important, women were ultimately not willing to forgo 6-months of protection in order to have other desired characteristics.…”
Section: Discussionmentioning
confidence: 77%
“…Some women also reported that partners could feel the ring, leading some to preemptively remove the ring prior to sex (28). While studies in women and providers in a range of geographies reported preinsertion concerns about a partner's discomfort during sex, actual reported impacts on daily life and sexual experience were minimal (17,18,29,30). Nevertheless, for some women an intravaginal ring will not be a viable option due to challenges with ring insertion, perceptions of anatomical incompatibility, and/or perceived or experienced discomfort by a sexual partner.…”
Section: Discussionmentioning
confidence: 99%